Traumatic avulsion of kidney and spleen into the chest through a ruptured diaphragm in a young worker: a case report - Konstantinos, Stamatiou (BioMed Central, 2007)
INTRODUCTION: Rupture of the diaphragm is almost always due to major trauma. Diaphragmatic injuries are rare (5–7%), usually secondary to blunt, or more rarely to penetrating, thoracic or abdominal trauma. No single investigation provides a reliable diagnosis of diaphragmatic rupture when a patient first arrives at hospital. Almost 33% are suspected on initial chest x-ray, but the percentage is lower in patients who are immediately intubated. Mortality in patients with diaphragmatic rupture following blunt abdominal trauma is generally associated with coexistent vascular and visceral injuries that could be rapidly fatal. It's mandatory that the right diagnosis is reached as soon as possible given that mortality is influenced by the time elapsing between trauma and diagnosis. CASE PRESENTATION: A 35-year-old worker was hit by a heavy object while working in the factory. He was transferred immediately to our emergency room. Chest x-ray showed massive left hemothorax without any additional signs to suggest diaphragmatic injury. It was decided to perform immediate surgical exploration before further radiological examination. During surgery, the right kidney and liver appeared normal, but the left kidney and spleen were not found in their anatomical position. The left hemidiaphragm had a10-cm oblique posterior tear. The left kidney was found lacerated in the left side of the chest, separated completely from its vascular pedicle and ureter, along with the entire spleen which was also separated from its vascular tree. CONCLUSION: The avulsion of both kidney and spleen following abdominal trauma is uncommon and survival depends on prompt diagnosis and treatment.